ARTIKEL ILMIAH: ANATOMI, BAHASA, DAN KESALAHANNYA - Syamsul Ghufron (EDU-KATA, 2014)
This study is aimed to describe papers’ anatomy, language, and error. This research uses descriptive qualitative method that describes all elements related to the research objectives and literary methods. The data of this study is the anatomy of paper, the language of scientific articles, and errors found in scientific articles. The data sourcesare scientific articles which are submitted to the journal editor of Humanis, Humanitas, Penabastra, and Edu-Kata. Data are collected by scrutinizingmethods through jotting down technique. Dataanalysis is done qualitatively and interpreted by gathering all collected data, then reducing them and finally presenting the result. The anatomy of the paperconsist of title, authorshipline (the author's name and the name of the institution where the author works), abstract and keywords, content or text body, conclusions and suggestions, acknowledgement, and bibliography.Language used in paper applies an official language. The errors of paper writing are distinguished on anatomical errors (title, abstract, discussion, conclusions, citations and bibliography) and language errors (including paragraphs, sentences, diction, and spelling).